Chemical profiling, antioxidant, and antibacterial properties of Tropaeolum majus L. extract as a functional food ingredient - Aguilera-Angel, Eliana-Yissel; Ballesteros-Vivas, Diego; Vera-Bravo, Ricardo; García, Néstor; Robles-Camargo, Jorge-Eliecer; Costa, Geison Modesti; Espinal-Ruiz, Mauricio; Caicedo-Trejos, Juan Pablo; Camacho, Ana Karina Carrascal; Arroyo-Maya, Izlia-Jazheel; Ibáñez, Elena; Cifuentes, Alejandro; et al. (Frontiers in Nutrition, 2025)
BackgroundNasturtium (Tropaeolum majus L.) is an edible plant that contains a diverse array of bioactive compounds, including phenolics, glucosinolates, and their hydrolysis products, isothiocyanates. Despite its functional potential, the plant remains largely underutilized, as it is predominantly cultivated as an ornamental species. Its limited incorporation into food products is primarily attributed to the sulfurous odor and pungent, bitter taste generated by glucosinolate degradation products. Concentrating these bioactive compounds through extraction offers a promising approach to reduce the quantity of plant material needed for functional enrichment.MethodsThe aim of this study was to identify the bioactive compounds and functional potential of nasturtium leaves and flowers collected in Cogua, Cundinamarca (Colombia). For this purpose, fresh samples were harvested, processed, and subjected to a preliminary phytochemical analysis. Methanolic and ethanolic extracts were prepared, and total glucosinolates, phenolics, and flavonoids were quantified. Chemical profiling was performed using UHPLC-q-TOF-MS/MS, while functional properties were assessed through antioxidant and antibacterial assays.ResultsThe ethanolic extract (70% v/v ethanol/water) from leaves retained phenolic compounds (2.10 ± 0.19 g GAE/g DS) and flavonoids (0.15 ± 0.02 g QE/g DS) which are linked to antioxidant activity, and benzyl glucosinolate (8.47 ± 1.68 μmol SE/g DW), whose hydrolysis product, benzyl isothiocyanate, is associated with antibacterial effects. Consistent with this, Enterococcus faecalis (Gram-positive) showed the lowest minimum inhibitory concentration (MIC, 15.6 mg/mL), while Escherichia coli and Salmonella Typhimurium (Gram-negative) exhibited MICs of 31.3 mg/mL.ConclusionThis study provides the first report of glucosinolate content in nasturtium cultivated in Colombia and describes the preparation and characterization of an extract obtained with generally recognized as safe (GRAS) solvents. The findings highlight its potential application in functional foods and nutraceuticals.